GENETIC APPROACHES FOR ENGINEERING BIOTIC STRESS RESISTANCE IN POTATO (Solanum Tuberosum L.) - A. BAKHSH1; S. D. DANGOL; M. NAEEM; M. H. AZIMI; A. YASMEEN (Journal of Animal and Plant Sciences, 2020)
Potato is one of the most important food crops in terms of annual production and food security worldwide. The crop is affected by several types of biotic stresses, e.g. insects, viruses, fungus, nematodes and weeds, which are the prominent limiting factors for its production. The conventional breeding methods in potato have been associated with limitations; none of the present day commercial cultivar has built-in resistance against biotic stresses. There is strong need for the development of new resistant potato varieties to cope against biotic stresses using non-classical approaches in combination with classical methods. The scientific literature suggests the contribution of modern biotechnological techniques for the development of transgenic potato lines resistant against insects and diseases. The present comprehensive review describes different genetic engineering approaches for the development of transgenic potatoes resistant to insects, weeds, nematodes, fungus and viruses by fellow researchers worldwide. It also gives an insight into modern technologies, e.g. RNAi and CRISPR-Cas9, which have emerged recently and can be implemented in the development of biotic stress resistant potato cultivars.
Keywords: Biotic stress; transgenic technology; crop productivity; genetic approaches